Fabrication and characterizations of recycled aluminium-copper-cullet powder (AL-CU-CP) metal composite - Nuhu, Awwal Hussain (2020)
Aluminium-Copper-Cullet powder (Al-Cu-CP) metal composite was fabricated from recycled materials, using recycled Aluminium (Al) obtained from scrap door and window frames, copper (Cu) wire scrap and cullet powder (CP). The research focused on fabricating the composite with improved properties which are incomparable with the constituent elements and other composites of similar components by using these inexpensive raw materials. This research is an attempt in removing solid wastes from the environment, promoting technological sustainability and also to support the zeroemission campaign for promoting green technology. The Al-Cu-CP metal composite was fabricated via stir casting method due to its simplicity and economic importance. The composite was produced with variable percentage compositions, melt holding times and casting temperatures. The composite and the unreinforced Al were analysed for physical, mechanical and morphological properties, phase analysis as well as for their chemical composition. The analyses indicated that the chemical composition of the products covered all the initial components. The optimum parameters were established as 20 wt. % of reinforcement materials (Cu and CP), 60 minutes of melt holding time and at 800 °C of casting temperature. The results of hardness tests were found to have improved significantly from 41.625 HV of the unreinforced Al to 124.704 HV for Al-Cu-CP metal composite. XRD results revealed formation of some intermetallics within the composite which strengthens the composite further. The AlCu-CP metal composite has shown appreciable level of wear resistance and corrosion resistance in artificial seawater (3.5 g/L NaCl) at room temperature. Heat treatment further improved these properties of the Al-Cu-CP metal composite in all aspects. Due to these enhanced properties of Al-Cu-CP composite, it could be used where high strength with less density product is required such as automobile brake shoes and brake disc as a result of the upgraded physical and mechanical properties.